Role of surfactant-induced Marangoni stresses in retracting liquid sheets - Constante-Amores, CR; Chergui, J; Shin, S; Juric, D; Castrejon-Pita, JR; Castrejon-Pita, AA (Cambridge University Press, 2022)
In this work, we study the effect of insoluble surfactants on the three-dimensional rim-driven retraction dynamics of thin water sheets in air. We employ an interface-tracking/level-set method to ensure the full coupling between the surfactant-induced Marangoni stresses, interfacial diffusion and inertia. Our findings are contrasted with the (Newtonian) dynamics of a liquid sheet edge, finding that the surfactant concentration can delay, or effectively prevent, the breakup of the rim. Our simulations use the fastest growing Rayleigh–Plateau instability to drive droplet detachment from the fluid sheet (rim). The results of this work unravel the significant role of Marangoni stresses in the retracting sheet dynamics at large elasticity numbers. We study the sensitivity of the dynamics to the elasticity number and the rigidification of the interface.